Підсумки інтродукції вітчизняних сортів троянд у Національному ботанічному саду ім. М.М. Гришка НАН України - Rubtsova, O.L.; Chizhan'kova, V.I.; Kuznetsova, T.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of introduction of rose cultivars of domestic parentage in M.M. Gryshko National Botanical Gardens are brought. The history of rose breeding in Ukraine has been presented.